(untitled) (Revista BOEM, 2024)
The present work, which is a theoretical-philosophical essay, aims to discuss the use of digital videos in teaching mathematics from a Wittgensteinian perspective, that is, from a theoretical perspective of some concepts presented in Ludwig Wittgenstein’s second philosophy. To this end, initially, we discussed digital videos in Education (Mathematics), seeking to highlight some of the potential of these resources in teaching mathematical concepts. Next, we make some considerations about Wittgenstein’s thought, highlighting aspects about the concepts of language games and seeing-how, and their relationships with mathematics teaching. Finally, we discuss digital videos in teaching and learning mathematics, seeking to link the potential and concepts mentioned above. It can be concluded that the video, as an activity that is intertwined with different linguistic manifestations, is a language game that can contribute to the appropriation and use of mathematical language, as well as to the training ofteachers who teach mathematics.